Function Of Kuda Lumping Art in The community Of Sungai Merah Village, Pelawan District, Sarolangun Regency, Jambi Province - Harefa, Oktaviani syahputri; Esy Maestro (Universitas Negeri Padang, 2024)
This research aims to find out the function of lumping horse art in the community of Sungai Merah Village, Pelawan Sub-district, Sarolangun Regency, Jambi Province. The type of research used is qualitative research using qualitative descriptive methods. Data sources are the head of Sungai Merah Village, elders of the lumping horse art group, members of the lumping horse art and the people of Sungai Merah Village. The research location is in Sungai Merah Village, Pelawan District, Sarolangun Regency. The data collection techniques used are literature study techniques, observation techniques, interview techniques and documentation techniques. Data analysis techniques used are data reduction, data presentation and conclusion drawing. The function theory used is Allan P. Meriam's function theory. The results showed that the elements of kuda lumping art consist of actors, movements, musical instruments, costumes, makeup and properties. The structure of the show consists of opening, core, and closing. the functions in the art of lumping horse in Sungai Merah Village are: function of emotional expression, function of aesthetic pleasure, function of entertainment, function of communication, function of physical reaction, function of contribution to the sustainability and stability of culture, function of community integration.